Implementasi Sistem Informasi Absensi Siswa dan Guru Berbasis Web Menggunakan QR Code di SMP Negeri 2 Kudus - Bahtiar, Adhi; Arifin, Muhammad (Al-DYAS, 2026)
Digital transformation in school attendance processes continues to advance, yet studies on the implementation of web-based attendance systems using QR Code scanning at regional lower secondary schools remain limited. This study aims to evaluate the implementation of a web-based Student and Teacher Attendance Information System using QR Code at SMP Negeri 2 Kudus in improving the accuracy of attendance recording, accelerating recap processes, and reducing reliance on manual record-keeping. The research employed a qualitative approach with a descriptive case study design, involving five respondents consisting of the system operator and four student representatives. Data were collected through observation of attendance activities, structured interviews, and analysis of attendance recap documents before and after system implementation. The findings show that the QR Code-based attendance system is capable of accelerating the daily attendance process by up to 70 percent, reducing the potential for data duplication and manipulation by 87 percent, and enhancing the readability and real-time availability of attendance reports. In addition, users reported a satisfaction level of 82 percent, particularly regarding ease of access and the practicality of using QR Codes. These results indicate that the success of the implementation is influenced by the alignment of system features with user needs and the support of school infrastructure. The study concludes that digitizing attendance through QR Code represents an effective model for improving the quality of attendance administration in regional lower secondary schools and provides practical insights for other institutions seeking to adopt similar systems.